Multicenter Retrospective Registry of Anterior Communicating Artery Aneurysms with Endovascular Therapy (MACAARET): safety and efficacy study according to morphological considerations and spatial orientations. Issue 10 (October 2021) - Zarco, F.; Macías, N.; Delgado, F.; Rosati, S.; González, A.; Jimenez, E.; Moreu, M.; Ortega, J.; Macho, J.; López-Rueda, A.
Abstract : AIM: To analyse the safety and efficacy parameters of endovascular treatment of anterior communicating artery (ACoA) aneurysms, according to their morphological considerations and three-dimensional orientation in a multicentric registry. MATERIALS AND METHODS: A retrospective analysis was undertaken of a prospective database of consecutive patients that underwent endovascular embolisation for ACoA aneurysm in four high-volume neuroradiology interventional departments. The study has been registered in ClinicalTrial.gov. Data were collected regarding the clinico-demographic variables of the patients, anatomical variations of the circle of Willis, morphological considerations and spatial orientation of ACoA aneurysms were recorded. Safety and efficacy variables were also recorded. Associations between anatomical variations of the circle of Willis, morphological considerations, and spatial orientation of the ACoA aneurysms and safety and efficacy variables were assessed. RESULTS: Data from 122 consecutive patients were collected in the MACAARET study (mean age (±SD) was 55 (±14) and 50.8% (62/122) were male). One hundred and five patients (86.1%) presented with subarachnoid haemorrhage (SAH). ACoA aneurysms with a neck size of >4 mm had less chance of having successful endovascular treatment than those of ≤4 mm (19.8% versus 46.7%; p= 0.002) and were also more likely to recanalise during follow-up (61.5% versus 19.5%; p= 0.003). Moreover, ACoA aneurysms with an aspect ratio of >1.7 had more chance of having immediate therapeutic success than those with a ratio of ≤1.7 (70.7% versus 44.8%; p= 0.012). There were no other associations between the anatomical variables of the ACoA aneurysms and the safety–efficacy variables. CONCLUSION: ACoA aneurysms are suitable for both endovascular and microsurgical approaches, but more data are required to determine which is the best approach regarding the morphological and spatial orientation of the aneurysm and the anatomical variations of the circle of Willis. Highlights: ACoA aneurysms over 4 mm neck are less prone to successful endovascular treatment. ACoA aneurysms over 4 mm neck are more prone to recanalize during the follow-up. ACoA aneurysms with ASPECT ratio>1.7 are more prone to immediate therapeutic success. ACoA aneurysms: Morphological consideration was not associated to endovascular treatment. ACoA aneurysms: Spatial orientation was not associated to endovascular treatment.